Restorative Justice as an Effort to Settle Traffic Accident Crime Cases - I Gusti Gede Maha Andika Jaya; Faisal Santiago; Zudan Arief Fakrulloh (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
ABSTRACT The traffic problems occurred of traffic accidents that result in human casualties and/or property loss. Law enforcement systems development and methods in Indonesia shows a tendency to follow the development of the general justice system, especially the development of the principle of restorative justice by burdening executant with their mistakes, apologize, returning damages and losses to victims as before or resembles condition. The formulation of the problem in this study is how the traffic accident crimes can be resolved through restorative justice, what is the investigator's consideration in resolving traffic accident cases through restorative justice. From the results of the study it can be concluded that the traffic accidents can be resolved through restorative justice according to Article 236 (2) of Law No. 22 of 2009, namely only minor traffic accidents, according to Article 63 of Law Police Regulation Number 15 of 2013, which is a minor traffic accident, and based on the letter of the National Police Number 8 of 2018, which is a crime that does not cause human casualties. The investigator's consideration in resolving traffic accident cases through restorative justice is the existence of a peace agreement by both parties involved in the traffic accident. Keywords : Accident Cases